Molecular Dynamics Analysis of the Conformations of a β-hairpin Miniprotein - Hatfield, Marcus P. D. (2010)
Molecular Dynamics simulations of a β-hairpin miniprotein, CLN025, were performed to examine the conformational stability of the peptide in H(2)O at 278 K, 300 K, 333 K and 363 K as well as in TFE, MeOH and DMSO at 300 K. CLN025 is a variant of the Chignolin miniprotein, in which the terminal Gly residues of Chignolin are replaced with Tyr residues, which leads to a 29.7 K increase in melting temperature. The energy of the intramolecular interactions were calculated using DFT quantum chemical calculations at the BH and HLYP/cc-pVTZ level of theory. CLN025 maintained a β-hairpin conformation in all environments. The β-hairpin is stabilized by hydrogen bonds, an electrostatic interaction between the charged termini of the peptide and weakly polar interactions. The interaction between the backbones of the N and C-terminal strands accounts for −97.32 to −120.87 kcal mol(−1) of the stabilization energy. The energy of the CH-π interactions between Tyr2 and Pro4 were between −1.80 and −8.9 kcal mol(−1) and the energy of the Tyr2-Trp9 Ar-Ar interaction was between −0.43 and −8.11 kcal mol(−1). Increasing temperature caused the Tyr2-Pro4 CH-π and the Tyr2-Trp9 and Tyr2-Tyr10 Ar-Ar interactions to become less favorable but the Tyr1-Trp9 interaction became more favorable and played an important role in stabilizing the β-hairpin of CLN025 that resulted in the increased melting temperature. The weakly polar interactions play an important role in the structure and stability of CLN025 and other proteins.